The Influence of Product Completeness on Consumer Purchase Decisions at Supermarkets 88 Bengkalis (Case Study on Bengkalis City Community) - Neli Nurzana; Bustami Bustami (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study aims to determine the effect of product completeness on purchasing decisions and to determine the influence of product completeness on consumer purchasing decisions at 88 Bengkalis supermarkets. The object in this study is the 88 Bengkalis self-service consumers consisting of 42 men and 58 women. The type of research used in this research is associative research by distributing questionnaires to 100 respondents using nonprobability sampling with snowball sampling method. The test results show that product completeness has a positive and significant effect on purchasing decisions, meaning that the product completeness variable is one of the variables that can be used to measure purchasing decisions.The determinant coefficient (KD) is 0.578 or equal to 57.8%, which means that product completeness affects purchasing decisions. amounted to 57.8%, the rest is influenced by other variables not examined in this study. The result of the T test shows that the t value of 11, 582 is greater than the t-table of 1.984, which means that completeness of the product has a positive and significant effect on Consumer purchasing decisions.